The evil necessity : British naval impressment in the eighteenth-century Atlantic world - Brunsman, Denver Alexander, 1975- (Early American histories., 2013)
CONTENT: Part I. Empire -- Imperial Design -- Ruling the Waves -- Cultures of Impressment -- Part II. Sailors -- Men of War -- Everyday Escapes -- Atlantic Impressment Riots -- Epilogue.